International Child Abduction: The Complexities of Forensic Psychiatric Assessments Before the Hague Convention - Patel, Mitesh; Baldeo, Shawn; Swartz, Pip; Glancy, Graham (Frontiers in Psychiatry, 2021)
The Hague Convention is an international intergovernmental agreement that facilitates the return of abducted children to lawful parents across international borders. Children may not be returned if it can be established that the return would result in harm to the child. Forensic psychiatrists may be called upon to provide an expert opinion regarding the potential harm to come to a child, as well as various other psycholegal issues. We discuss interpretations and precedents regarding this law and the possible contributions of forensic psychiatrists. We also discuss two hybridized case examples involving international child abduction and proceedings before the Hague Convention. We will discuss issues that arose after psychiatric evaluations in each case.